Seasonal variations in the lipid and fatty acid composition of the euphausiid Meganyctiphanes norvegica from the Ligurian Sea - Mayzaud, P; Virtue, P; Albessard, E (Marine Ecology Progress Series, 1999)
Lipid and fatty acid composition of the northern krill Meganyctiphanes norvegica from the Mediterranean Sea were studied with respect to sex and season. Detailed composition of the lipid classes is reported for both males and females during the spring reproductive season and the late summer non-reproductive season. Both sexes showed similar lipid structure, with neutral lipids dominated by triacylglycerols. Polar lipids were dominated by phosphatidylcholine. Fatty acid compositions of both polar lipids and triacylglycerols showed little change with sex or season. Polar lipids were dominated by HUFA (20:5n-3 or EPA and 22:6n-3 or DHA) as well as palmitic and oleic acid. Neutral lipid fatty acid profiles were dominated by 22:6(n-3) and palmitic acid, with a significant contribution of oleic, myristic, stearic and vaccenic acids as well as 20:5(n-3). Seasonal changes in total lipids showed maximum accumulation in early summer and minimum levels in early winter. Changes in fatty acid composition appeared related to the succession of populations with varying levels of triacylglycerols, as illustrated by the contrast between the early winter and spring periods in a correspondence analysis. Increased proportions of myristic, palmitoleic and 18:4(n-3) acids during the spring period are characteristic of the triglyceride fraction while the main descriptor of the winter period is DHA, which is the key constituent of the polar lipids. Comparison with literature data illustrated the clear decrease in lipid content of northern krill with latitude and the specific nature of the seasonal pattern recorded in the Ligurian Sea. The regional variability in fatty acid composition and the significance of fatty acids as potential markers of feeding behaviour are discussed in relation to the omnivorous character of M. norvegica.